The Philosophical Thought of the Prophetic Law in the Indonesian Legal System - Zuliyah, Siti; Shalihah, Fithriatus; Suryadi, Suryadi; Megawati, Megawati; Putri, Uni Tsulasi; Nugroho, Rahmat Muhajir (Տիգրան Մեծ)
In Indonesia, the positivistic modern ideologyis currentlyexperiencing a downfall due to its inability to overcome the problems of human life. This study aims to complete the explanation of why prophetic law is needed in the Indonesian legal system in the juridical domainand the implementationdomain. This was qualitative research which used a philosophical juridical approach. This paper used a de-scriptive method of analysis. In Indonesia, theprophetic law refers to the ideology of Pancasila, which is interpreted as the nation‟s way of life. Itreveals the relationship between humans and God, the relationship among humans, and the relationship between humans and the universe. The basis for the thought and implementationof prophetic law in Indonesia is the first principle of Pancasila and the Preamble to the 1945 Constitution, whichstatedthat the proclamation of Indone-sianindependence was ablessing fromAllah (God) Al-mighty. In addition, based on Law No. 48 of 2009 concerning Judicial Power, it is stated that the judiciary is carried out “for the sake of justice based on the Belief in One God,”which is the soul of decisionsmadeby judicial bodies in Indonesia.
Keywords: Philosophy of law